Strategic design and synthesis of AIEE (Aggregation Induced Enhanced Emission) active push-pull type pyrene derivatives for the ultrasensitive detection of explosives - Joshi, Mayank; Choudhury, A.R. (Elsevier, 2019)
Tuning of solid and solution phase emission with simple push-pull ‘Aggregation Induced Enhanced Emission’ (AIEE) pyrene compounds for deeper understanding on the mechanism for selectivity and sensitivity towards the nitro explosives with lowering the detection limit upto ppt (parts per trillion) level.
Only IISERM authors are available in the record.
Keywords: Ultrasensitive explosive detection; Photo induced electron transfer and energy mechanism; Enhanced; Emission